Schwartz Centre Rounds: qualitative exploration of panel members' experiences within a forensic mental health service. (April 2023) - Groves, Emma; Collinson, Rachel; Hegarty, Amy; Hamad, Elshiema; Asadi, Tyler-Dee; Ejara, Abebe; Kudsia, Lubna; Shah, Shivali
Abstract : Schwartz Centre Rounds (SCRs) provide a structured forum for staff from all disciplines to meet and discuss the difficult emotional and social challenges that arise in caring for patients. Research into the implementation of SCRs has shown that staff who attend report increased insight into the emotional and social aspects of care; greater understanding of the roles of their colleagues; improved teamworking and decreased feelings of isolation and stress. However, little research has explored the implementation of SCRs within forensic settings, and no research has focused solely on the experiences of panel members. Three focus groups were facilitated with participants who had participated in a SCR panel within a forensic mental health service. Semi-structured interviews were carried out, audio-recorded and subsequently transcribed. Interpretive phenomenological analysis was utilised to analyse the transcripts, and four key themes were identified. These themes were: feeling vulnerable, the importance of validation, exposure to intense emotional experiences and improved understanding and connection. We conclude that SCRs can be an emotionally challenging but rewarding experience, with the potential to enhance teamworking and general well-being. Limitations and recommendations for future research are also discussed.